Lie Triple Derivations on 𝒥-Subspace Lattice Algebras - Ting Wang; Fangyan Lu (Abstract and Applied Analysis)
We describe the structure of Lie triple derivations on 𝒥-subspace lattice algebras. The results can be applied to atomic Boolean subspace lattice algebras and pentagon subspace lattice algebras, respectively.